Multilayer structure including insulating layer
Patent Information
- Application Number
- JP2024025889
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-14
- Filing Date
- 2024-02-22
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2042-10-12
AI Technical Summary
【0016】 本発明では、低い誘電率、誘電正接と低い吸水率、高い絶縁性を示す絶縁層を、高い接着強度(剥離強度)を以って銅箔平滑面と接着することで、高周波多層基板として有用な多層構造体を提供することができる。
Smart Images

Figure 0007638410000006 
Figure 0007638410000007 
Figure 0007638410000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a multilayer structure having an insulating layer made of a composition having high adhesion to the smooth surface of a copper foil. [Background technology]
[0002] As communication frequencies move to the gigahertz band and higher, there is an increasing need for multilayer substrates made of CCL or FCCL containing insulating materials with low dielectric properties. Fluorine-based resins such as perfluoroethylene have the characteristics of excellent low dielectric constant, low dielectric loss, and excellent heat resistance, but are difficult to mold and form into films, and also have problems with adhesion to copper foil in wiring, making them difficult to apply to multilayer substrates. On the other hand, substrates and insulating materials using post-curing resins such as epoxy resin, unsaturated polyester resin, polyimide resin, and phenol resin have been widely used due to their heat resistance and ease of handling, but their dielectric constant and dielectric loss are relatively high, and improvements are needed as insulating materials for high frequencies (Patent Document 1).
[0003] Therefore, attention has been focused on hydrocarbon-based resins that have inherently low dielectric properties. In order to make a hydrocarbon-based resin, which is originally a thermoplastic resin, into a curable resin, it is necessary to introduce a functional group, but functional groups that generally react to radicals or heat have polarity, which deteriorates the low dielectric properties. When attempting to introduce a functional group composed only of a hydrocarbon, for example, an aromatic vinyl group, in many cases, an intermolecular reaction between expensive hydrocarbon-based monomers is utilized (Patent Document 2), which is often not economical. Patent Document 3 shows a cured body obtained from a specific coordination polymerization catalyst and consisting of an ethylene-olefin (aromatic vinyl compound)-aromatic polyene copolymer and a non-polar vinyl compound copolymer having a specific composition and blend. In the case of this technology, only one of the two vinyl groups of the aromatic polyene (divinylbenzene) is selectively copolymerized and the remaining vinyl group is preserved, so that a hydrocarbon-based copolymer macromonomer having a functional group of an aromatic vinyl group can be easily obtained. The cured products obtained from compositions of similar olefin-aromatic vinyl compound-aromatic polyene copolymers and auxiliary materials have the characteristics of low dielectric constant and low dielectric loss tangent, and a wide range of physical properties from soft to hard can be imparted by selecting the composition and appropriate auxiliary materials (Patent Documents 4 and 5). In addition, as shown in the examples, these materials can exhibit high adhesion (adhesive strength) to the roughened surface of copper foil. Therefore, they are considered to be suitable for various substrate materials and insulating materials for high-frequency signals.
[0004] However, particularly in the case of applications such as high-frequency transmission lines such as microstrip lines, antennas, and interlayer insulating materials and coverlays for multilayer boards, the insulating material is in contact with the smooth surface of the copper foil, and high adhesive strength (peel strength) with the smooth surface of the copper foil is required. In particular, at least a portion or at least one surface of a sheet-shaped or film-shaped interlayer insulating material is in contact with the smooth surface of the copper foil, and high adhesive strength with this is required. However, the published patent documents do not disclose any technology for imparting high adhesiveness (adhesive strength) to an insulating material with respect to the smooth surface of the copper foil. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 6-192392 [Patent Document 2] JP 2004-087639 A [Patent Document 3] JP 2007-217706 A [Patent Document 4] International Publication No. 2021 / 112087 [Patent Document 5] International Publication No. 2021 / 112088 Summary of the Invention [Problem to be solved by the invention]
[0006] In contrast to the above-mentioned conventional techniques, it is desirable to provide a multilayer structure useful as a multilayer substrate having an insulating layer I (also referred to as "interlayer insulating material" in this specification) that exhibits high adhesive strength to a smooth copper foil surface. [Means for solving the problem]
[0007] That is, the present application provides the following aspects that solve the above problems.
[0008] Aspect 1. one or more insulating layers; One or more resin layers; At least one copper foil having a smooth surface and a roughened surface; A multi-layer structure comprising: the insulating layer comprises an olefin-aromatic vinyl compound-aromatic polyene copolymer and a surface modifier; the resin layer includes at least one selected from the group consisting of polyimide (PI), liquid crystal polymer (LCP), polyphenylene ether (PPE), polyfunctional aromatic vinyl resin (ODV), epoxy resin, and a composition the same as that of the insulating layer; At least one surface of each of the insulating layers is bonded to a smooth surface of the copper foil; For each of the resin layers, at least one surface of the resin layer is bonded to the roughened surface of the copper foil and the resin layer is not bonded to the smooth surface of the copper foil, or both surfaces of the resin layer are not bonded to the copper foil. A multi-layer structure characterized by:
[0009] Aspect 2. The multilayer structure of aspect 1, wherein at least one surface of the insulating layer has a recessed portion with respect to the lamination direction, and the copper foil is adhered to the recessed portion so that a portion of the surface is adhered to the smooth surface of the copper foil and another portion of the surface is adhered to the resin layer.
[0010] Aspect 3. 3. The multilayer structure of claim 1 or 2, wherein the surface modifying agent is a silane coupling agent.
[0011] Aspect 4. The multilayer structure according to any one of aspects 1 to 3, wherein the olefin-aromatic vinyl compound-aromatic polyene copolymer satisfies all of the following conditions (1) to (4): (1) The number average molecular weight of the copolymer is 500 or more and less than 100,000. (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of aromatic vinyl compound monomer units is 0 to 70% by mass or 0 to 98% by mass. (3) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of vinyl groups and / or vinylene groups derived from aromatic polyene units is 1.5 or more and less than 20 per number average molecular weight. (4) The olefin is one or more olefins selected from olefins having 2 to 20 carbon atoms, the content of the olefin monomer units is 10% by mass or more, and the total of the olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is 100% by mass.
[0012] Aspect 5. The multilayer structure according to any one of aspects 1 to 4, wherein the insulating layer further comprises one or more selected from the following (a) to (c): (a) Hardener (b) One or more resins selected from the group consisting of hydrocarbon elastomers, polyphenylene ether resins, and aromatic polyene resins. (c) Polar monomers
[0013] Aspect 6. The multilayer structure according to any one of aspects 1 to 5, wherein the content of the surface modifier in the insulating layer is 0.001 to 10 parts by mass per 100 parts by mass of the olefin-aromatic vinyl compound-aromatic polyene copolymer.
[0014] Aspect 7. A cured multilayer structure obtained by curing the multilayer structure according to any one of aspects 1 to 6.
[0015] Aspect 8. A high frequency transmission line, a multi-layer CCL substrate, a multi-layer FCCL substrate, an antenna, or a coverlay comprising the cured multi-layer structure of embodiment 7. Effect of the Invention
[0016] In the present invention, an insulating layer exhibiting a low dielectric constant, dielectric tangent, low water absorption, and high insulation properties is bonded to a smooth surface of a copper foil with high adhesive strength (peel strength), thereby providing a multilayer structure useful as a high-frequency multilayer substrate. [Brief description of the drawings]
[0017] [Figure 1] 1 shows the structure of a basic unit that may be included in some or all of the multi-layer structure of the present invention. [Diagram 2] Specific examples of structures that may be included in part or all of the multilayer structure according to the present invention are given below. [Diagram 3] Specific examples of structures that may be included in part or all of the multilayer structure according to the present invention are given below. [Figure 4] A modified example of the above basic unit will be described. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The multilayer structure has, as its basic unit, a structure including a copper foil, a resin layer adhered to the roughened surface of the copper foil, and an insulating layer adhered to the smooth surface of the copper foil (as shown in FIG. 1). The multilayer structure may include one or more of the basic units, or may include a combination of the basic unit and another layer.
[0019] The (one or more) insulating layers contained in the multilayer structure are a concept that includes interlayer insulating materials and coverlays. Furthermore, the interlayer insulating material is a concept that includes the concepts of interlayer adhesives and bonding sheets. The sheet is also intended to include the concept of a film. Furthermore, even if a film is described in this specification, the concept of a sheet is also intended to be included. The composition according to the present invention will be described in more detail below. In this specification, the composition is a concept that includes a varnish. In other words, among compositions, a composition that is particularly liquid is described as a varnish.
[0020] <Copper foil and roughened surface> The (one or more) copper foil contained in the present multilayer structure may be any copper foil that can be used for wiring or a substrate. The thickness is not particularly limited, but is generally in the range of 1 to 500 μm, preferably 5 to 50 μm. A copper foil that is compatible with high frequencies is preferable, and may be a rolled copper foil or an electrolytic copper foil. The present copper foil has a roughened surface (also called a matte surface, which may be written as an M surface) and a smooth surface (also called a glossy surface or a shine surface, which may be written as an S surface). For example, the roughened surface of the copper foil may be a copper foil having a surface roughness (maximum height) Rz as defined in JIS B0601:2001 of preferably 5 μm or less, particularly preferably 3 μm or less. For example, the roughened surface of the copper foil may be a copper foil having a surface roughness (maximum height) Rz as defined in JIS B0601:2001 of preferably more than 0.5 μm. Such copper foils can be obtained from Furukawa Electric Co., Ltd., JX Nippon Mining & Smelting Co., Ltd., Mitsui Mining & Smelting Co., Ltd., and the like.
[0021] <Copper foil smooth surface> The smooth surface of copper foil is a surface of copper foil used for wiring or substrate that is not roughened and is relatively smoother than the roughened surface. The smooth surface generally has a surface roughness (maximum height) Rz of 0.5 μm or less as specified in JIS B0601:2001, but is not particularly limited since it is a surface that is relatively smoother than the roughened surface or has a relatively high gloss as described above. Those skilled in the art can easily recognize and distinguish between the smooth surface and the roughened surface of copper foil. The roughened surface of copper foil is used to bond to the base film or substrate, so the interlayer insulating material of the multilayer substrate is required to have high adhesion to the remaining smooth surface.
[0022] <Resin layer> The resin layer (one or more) contained in the multilayer structure is a resin layer selected from polyimide (PI), liquid crystal polymer (LCP), polyphenylene ether (PPE), polyfunctional aromatic vinyl resin (ODV), epoxy resin, or the same resin (composition) as the insulating layer. It is generally a component of a substrate that is a part of the multilayer structure, and is distinguished from the insulating layer by adhering to the roughened surface of the copper foil and not adhering to the smooth surface of the copper foil or not adhering to the copper foil at all. Here, the case where the resin layer has the same composition as the insulating layer means that the resin layer "contains an olefin-aromatic vinyl compound-aromatic polyene copolymer and a surface modifier" like the insulating layer. The thickness of the resin layer is arbitrary, and is preferably 10 μm to 1 mm. In addition, from the viewpoint of improving the strength of the structure and reducing the coefficient of linear expansion (CTE), it is preferable that the resin layer contains a reinforcing material such as a filler or glass cloth. One surface of the resin layer may be previously adhered to the roughened surface of the copper foil. The polyimide (PI) is a concept including modified polyimide (MPI) having a reduced dielectric constant, dielectric tangent and water absorption rate. As the polyphenylene ether, a curable PPE having a functional group is preferable.
[0023] <Preferred Structure> In a preferred embodiment, a part or all of the present multilayer structure has the basic unit shown in Fig. 1 or a repeating structure thereof, and may further have the insulating layer, the resin layer, or the copper foil. As a specific example, it may be composed of one or a combination of structures (1) to (5) shown in Fig. 2 or Fig. 3.
[0024] In one embodiment, a part or all of the basic units may be replaced by a modified version of the basic unit shown in FIG. 4. In another embodiment, a part or all of the structures (1) to (5) may be replaced by a modified version of the basic unit shown in FIG. 4. That is, at least one surface of the insulating layer may have a recessed portion in the lamination direction, and the copper foil may be bonded to fit in the recessed portion, so that a part of the surface is bonded to the smooth surface of the copper foil, and another part of the surface is bonded to the resin layer. That is, in this way, a configuration in which the resin layer is directly bonded to the insulating layer may be adopted. Such a replacement can be performed, for example, by partially removing the copper foil by etching and replacing that part with the insulating layer. In other words, the area of each layer included in this multilayer structure does not need to be constant, and for example, it may be divided into island shapes or have recesses. In addition, one or more of the layers of the present multilayer structure may have through holes or via holes (through hole vias, interstitial vias, blind vias, buried vias, etc.), but in this specification, these holes are excluded from the definition of the layer structure of the present multilayer structure (the presence of holes is omitted in the above drawings).
[0025] <Insulating layer> The thickness of the insulating layer contained in the multilayer structure is arbitrary, but is generally 1 μm to 500 μm, preferably 5 μm to 100 μm. The composition forming the insulating layer contained in the multilayer structure contains an olefin-aromatic vinyl compound-aromatic polyene copolymer as a main component, and further contains a surface modifier, preferably a silane coupling agent, in an amount of 0.01 to 5 parts by mass per 100 parts by mass of the olefin-aromatic vinyl compound-aromatic polyene copolymer. At least a part of the insulating layer contacts the smooth copper foil surface. When there are multiple insulating layers, at least one surface of each of the insulating layers contacts the smooth copper foil surface (in other words, when there are multiple insulating layers, each of the insulating layers contacts the smooth copper foil surface). In an embodiment, it is preferable that none of the surfaces of the insulating layer is bonded to the roughened surface of the copper foil. The olefin-aromatic vinyl compound-aromatic polyene copolymer may be contained in an amount of 30% by mass or more, preferably 50% by mass or more, more preferably 70% by mass or more, based on the entire composition. The present olefin-aromatic vinyl compound-aromatic polyene copolymer can be obtained by copolymerizing each of the monomers of an olefin, an aromatic vinyl compound, and an aromatic polyene.
[0026] The olefin monomer is at least one selected from α-olefins having 2 to 20 carbon atoms and cyclic olefins having 5 to 20 carbon atoms, and is a compound consisting of carbon and hydrogen without substantially containing oxygen, nitrogen, or halogen. Examples of α-olefins having 2 to 20 carbon atoms include ethylene, propylene, 1-butene, 1-hexene, 1-octene, 1-decane, 1-dodecane, 4-methyl-1-pentene, and 3,5,5-trimethyl-1-hexene. Examples of cyclic olefins having 5 to 20 carbon atoms include norbornene and cyclopentene. The olefin preferably used is a combination of ethylene and an α-olefin other than ethylene or a cyclic olefin, or ethylene alone. When ethylene alone or the mass ratio of the α-olefin component other than ethylene contained / ethylene component is preferably 1 / 7 or less, more preferably 1 / 10 or less, the adhesive strength of the obtained cured body to copper foil or copper wiring can be increased, which is preferable. More preferably, the content of α-olefin monomer components other than ethylene in the copolymer is 6 mass% or less, and even more preferably 4 mass% or less, or the olefin is ethylene alone. In the preferred combination of ethylene and an α-olefin other than ethylene, the glass transition temperature of the finally obtained cured ethylene-α-olefin-aromatic vinyl compound-aromatic polyene copolymer can be freely adjusted within the range of approximately -60°C to -10°C depending on the type and content of the α-olefin.
[0027] The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and examples thereof include styrene, paramethylstyrene, paraisobutylstyrene, various vinylnaphthalenes, and various vinylanthracenes.
[0028] The aromatic polyene monomer is a polyene having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in its molecule, preferably various ortho-, meta-, and para-divinylbenzenes or mixtures thereof, divinylnaphthalene, divinylanthracene, p-2-propenylstyrene, p-3-butenylstyrene, and other aromatic vinyl structures, substantially free of oxygen, nitrogen, and halogen, and composed of carbon and hydrogen. In addition, bifunctional aromatic vinyl compounds such as 1,2-bis(vinylphenyl)ethane (abbreviation: BVPE) described in JP-A-2004-087639 can also be used. Among these, various ortho-, meta-, and para-divinylbenzenes or mixtures thereof are preferably used, and a mixture of meta- and para-divinylbenzenes is most preferably used. In this specification, these divinylbenzenes are referred to as divinylbenzenes. When divinylbenzenes are used as aromatic polyenes, they are preferred because they have high curing efficiency and are easy to cure when subjected to a curing treatment.
[0029] The above-mentioned olefin, aromatic vinyl compound, and aromatic polyene monomers may contain other polar groups, such as olefins containing oxygen atoms, nitrogen atoms, etc., aromatic vinyl compounds containing oxygen atoms or nitrogen atoms, or aromatic polyenes containing oxygen atoms or nitrogen atoms, etc., but the total mass of these monomers containing polar groups is preferably 10 mass% or less of the total mass of the composition, more preferably 3 mass% or less, and most preferably does not contain any monomers containing polar groups. By making it 10 mass% or less, the dielectric properties (low dielectric constant / low dielectric loss) of the cured body obtained by curing the composition can be improved.
[0030] The present olefin-aromatic vinyl compound-aromatic polyene copolymer preferably satisfies one or more of the following conditions (1) to (4), and more preferably satisfies all of them. (1) The number average molecular weight of the copolymer is 500 or more and less than 100,000. (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of aromatic vinyl compound monomer units is 0 to 98% by mass, preferably 0 to 70% by mass. (3) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of vinyl groups and / or vinylene groups derived from aromatic polyene units is 1.5 or more and less than 20 per number average molecular weight. (4) The olefin is one or more olefins selected from olefins having 2 to 20 carbon atoms, the content of the olefin monomer units is 10% by mass or more, and the total of the olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is 100% by mass.
[0031] The number average molecular weight (Mn) of the copolymer may be 500 or more and less than 100,000. In the present invention, the number average molecular weight of 500 or more and less than 100,000 means that the molecular weight calculated as standard polystyrene by GPC (gel permeation chromatography) falls within that range.
[0032] The content of aromatic vinyl compound monomer units contained in the copolymer may be 0% by mass or more and 98% by mass or less, more preferably 0% by mass or more and 70% by mass or less, and most preferably 10% by mass or more and 60% by mass or less. When the content of aromatic vinyl compound monomer units is 70% by mass or less, the glass transition temperature of the cured body of the finally obtained composition becomes lower than around room temperature, and toughness and elongation at low temperatures can be improved, which is preferable. When the content of aromatic vinyl compound monomer units is 10% by mass or more, the aromaticity of the copolymer is improved, compatibility with flame retardants and fillers is improved, bleeding out of flame retardants can be avoided, and the filling property of fillers can be improved. In addition, when the content of aromatic vinyl compound monomer units is 10% by mass or more, a cured body of the composition having high adhesive strength from copper foil or copper wiring can be obtained.
[0033] In the present copolymer, the content of vinyl groups and / or vinylene groups derived from aromatic polyene units (preferably the content of vinyl groups) may be 1.5 or more and less than 20 per number average molecular weight, preferably 2 or more and less than 20, and most preferably 3 or more and less than 20. When the content of vinyl groups and / or vinylene groups is 1.5 or more, the crosslinking efficiency is high, and a cured body with sufficient crosslinking density can be obtained. The content of vinyl groups derived from aromatic polyene units (divinylbenzene units) per number average molecular weight in the copolymer is calculated by the number average molecular weight (Mn) calculated in terms of standard polystyrene obtained by a GPC (gel permeation chromatography) method known to those skilled in the art, and 1 The vinyl group content derived from the aromatic polyene unit obtained by H-NMR measurement can be compared. For example, 1 By comparing the intensities of the peak areas obtained by H-NMR measurement, if the content of vinyl groups derived from aromatic polyene units (divinylbenzene units) in the copolymer is 0.45% by mass, and the number average molecular weight calculated as standard polystyrene by GPC measurement is 36,000, the molecular weight of the vinyl groups derived from aromatic polyene units in the number average molecular weight is the product of these, 162, which is divided by the formula weight of the vinyl groups, 27, to obtain 6.0. In other words, the content of vinyl groups derived from aromatic polyene units per number average molecular weight in this copolymer is found to be 6.0. The copolymer 1 The assignment of peaks obtained by H-NMR measurement is known from the literature. 1 A method for determining the composition of a copolymer from a comparison of peak areas obtained by H-NMR measurement is also known. 1 The H-NMR measurement method was performed in a known quantitative mode. 13 It is also possible to improve the accuracy of the composition by adding data on the peak areas and ratios of the C-NMR spectrum. In this specification, the content of divinylbenzene units in the copolymer is determined based on the peak intensity ( 1In other words, the content of divinylbenzene units is calculated from the content of vinyl groups derived from divinylbenzene units, assuming that one vinyl group is derived from one divinylbenzene unit in the copolymer.
[0034] In the present copolymer, the content of the olefin monomer unit is preferably 10% by mass or more, more preferably 20% by mass or more, and most preferably 30% by mass or more. The total of the olefin monomer unit, aromatic vinyl compound monomer unit, and aromatic polyene monomer unit is 100% by mass. When the content of the olefin monomer unit is 10% by mass or more, the toughness (elongation) and impact resistance of the finally obtained cured body are improved, and cracks during curing or cracks during a heat cycle test of the cured body are less likely to occur. In the present copolymer, the content of the olefin monomer unit is preferably 90% by mass or less.
[0035] In order to obtain preferred physical properties, the present copolymer may be a mixture of multiple types of copolymers. In the present copolymer, examples of suitable olefin-aromatic polyene copolymers that do not contain aromatic vinyl compound monomer units include ethylene-divinylbenzene copolymers, ethylene-propylene-divinylbenzene copolymers, ethylene-1-butene-divinylbenzene copolymers, ethylene-1-hexene-divinylbenzene copolymers, and ethylene-1-octene-divinylbenzene copolymers.
[0036] In the present copolymer, examples of the olefin-aromatic vinyl compound-aromatic polyene copolymer containing an aromatic vinyl compound monomer unit include an ethylene-styrene-divinylbenzene copolymer, an ethylene-propylene-styrene-divinylbenzene copolymer, an ethylene-1-hexene-styrene-divinylbenzene copolymer, and an ethylene-1-octene-styrene-divinylbenzene copolymer.
[0037] <Surface modifier> The composition of the present invention contains a surface modifier for the purpose of improving adhesion to copper foil for wiring. In particular, the purpose is to increase the adhesive strength (peel strength) to the smooth surface of copper foil. The amount (content) of the surface modifier used is preferably 0.001 to 10 parts by mass, more preferably 0.01 to 5 parts by mass, and most preferably 0.01 to 1 part by mass, per 100 parts by mass of the olefin-aromatic vinyl compound-aromatic polyene copolymer. If the amount of the surface modifier used is 10 parts by mass or less, the dielectric constant and dielectric loss tangent of the cured body obtained from the composition will be low, and the object of the present invention will be met.
[0038] In the present invention, a known surface modifier can be used. Examples of such surface modifiers include silane-based surface modifiers (also known as silane coupling agents), titanate-based surface modifiers, and isocyanate-based surface modifiers, and preferably silane-based surface modifiers are used. These surface modifiers may be used singly or in combination. Such silane-based surface modifiers can be obtained from Shin-Etsu Chemical Co., Ltd., Dow Corning, and Evonik. Silane-based surface modifiers are silane compounds having functional groups and hydrolytic condensable groups in the molecule. Examples of functional groups include vinyl groups such as vinyl, methacryloxy, acryloxy, and styryl, amino groups, epoxy groups, mercapto groups, sulfide groups, isocyanate groups, and halogens. Considering high adhesion to glass, the functional group is preferably one or more selected from vinyl groups, amino groups, epoxy groups, methacryloxy groups, and acryloxy groups, and most preferably one or more selected from amino groups, methacryloxy groups, and epoxy groups. These functional groups may be present in a single molecule or in multiple molecules. These surface modifiers may be used in one or more kinds. Examples of silane-based surface modifiers having a vinyl group as a functional group include vinyltrimethoxysilane and vinyltriethoxysilane. Examples of silane coupling agents having a styryl group as a functional group include p-styryltrimethoxysilane. Examples of silane coupling agents having an acryloxy group as a functional group include 3-acryloxypropyltrimethoxysilane. Examples of silane coupling agents having a methacryloxy group as a functional group include 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, and 3-methacryloxypropylmethyldiethoxysilane. Examples of silane coupling agents having an epoxy group as a functional group include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.Examples of silane coupling agents having an amino group as a functional group include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, bis(3-trimethoxysilylpropyl)amine, bis(3-triethoxysilylpropyl)amine, and N-(n-butyl)-3-aminopropyltrimethoxysilane. The above are examples having a methoxy group or an ethoxy group as a hydrolysis condensation group, but a triisopropoxy group or an acetoxy group can also be used. Particularly preferably, a silane-based surface modifier having, as a functional group, one or more groups selected from vinyl groups such as methacryloxy, acryloxy, and styryl, amino groups, epoxy groups, and mercapto groups is used.
[0039] The composition containing the copolymer and the surface modifier (hereinafter, simply referred to as "composition") can be prepared as follows. When the copolymer component is resinous, the surface modifier can be mixed by a known kneading method, for example, a twin-screw kneader, various rolls, various kneaders, etc. When the copolymer component is in the form of a varnish, it can be added to the varnish and stirred to mix and dissolve.
[0040] The composition of the present invention may further contain, in addition to the present copolymer and the surface modifier, (a) a curing agent, (b) one or more resins selected from a hydrocarbon-based elastomer, a polyphenylene ether-based resin, and an aromatic polyene-based resin, and (c) one or more polar monomers.
[0041] <(a) Hardener> As the curing agent that can be used in the composition of the present invention, it is possible to use a known radical generator or curing agent that can be used for polymerization or curing of conventional aromatic polyenes and aromatic vinyl compounds. Examples of such curing agents include radical polymerization initiators, cationic polymerization initiators, and anionic polymerization initiators, but preferably radical polymerization initiators can be used. Preferably, organic peroxides (peroxides), azo-based polymerization initiators, etc. can be freely selected depending on the application and conditions. A catalog listing organic peroxides can be downloaded from the NOF Corporation website, for example, https: / / www.nof.co.jp / business / chemical / chemical-product01. Organic peroxides are also described in catalogs of Fujifilm Wako Pure Chemical Industries, Ltd. and Tokyo Chemical Industry Co., Ltd. The curing agents used in the present invention can be obtained from these companies. Also, known photopolymerization initiators that use light, ultraviolet light, or radiation can be used as a curing agent. Examples of curing agents that use a photopolymerization initiator include a photoradical polymerization initiator, a photocationic polymerization initiator, and a photoanionic polymerization initiator. Such photopolymerization initiators can be obtained, for example, from Tokyo Chemical Industry Co., Ltd. Furthermore, curing by radiation or electron beam itself is also possible. Also, crosslinking and curing by heat of the raw materials contained therein can be performed without using a curing agent.
[0042] There is no particular limit to the amount of the curing agent used, but generally, 0.01 to 10 parts by mass per 100 parts by mass of the composition is preferred. The composition preferably excludes the curing agent and the solvent. When using a curing agent such as a peroxide or an azo-based polymerization initiator, the curing process is carried out at an appropriate temperature and time, taking into consideration its half-life. In this case, the conditions are arbitrary according to the curing agent, but generally, a temperature range of about 50°C to 200°C is appropriate.
[0043] The varnish of the present invention may contain component (b), i.e., "one or more resins selected from a hydrocarbon-based elastomer, a polyphenylene ether-based resin, and an aromatic polyene-based resin," preferably in an amount of 1 to 200 parts by mass per 100 parts by mass of the copolymer. The addition of component (b) has the effect of improving the mechanical properties of the cured product obtained from the varnish.
[0044] <Hydrocarbon elastomer> The amount of the hydrocarbon-based elastomer used in the composition of the present invention is preferably 1 to 200 parts by mass, more preferably 1 to 100 parts by mass, and most preferably 1 to 50 parts by mass, based on 100 parts by mass of the copolymer. The hydrocarbon-based elastomer that can be suitably used in the composition of the present invention preferably has a number average molecular weight of 100 to 100,000, more preferably 1,000 to 4,500. The hydrocarbon-based elastomer that can be suitably used in the composition of the present invention is preferably a single or multiple elastomers selected from ethylene-based or propylene-based elastomers, conjugated diene-based polymers, aromatic vinyl compound-conjugated diene-based block copolymers or random copolymers, and hydrogenated products thereof. Examples of the ethylene-based elastomers include ethylene-α-olefin copolymers such as ethylene-octene copolymers and ethylene-1-hexene copolymers, EPR, and EPDM, and examples of the propylene-based elastomers include atactic polypropylene, low stereoregular polypropylene, and propylene-α-olefin copolymers such as propylene-1-butene copolymer. These hydrocarbon elastomers may be modified, for example, by reacting them with a compound such as maleic anhydride to introduce a functional group.
[0045] Examples of the conjugated diene polymer include polybutadiene and 1,2-polybutadiene. Examples of the aromatic vinyl compound-conjugated diene block or random copolymer and their hydrogenated products (hydrogenated products) include SBS, SIS, SEBS, SEPS, SEEPS, SEEBS, etc. 1,2-polybutadiene that can be suitably used is available from Nippon Soda Co., Ltd. under the product names of liquid polybutadiene: B-1000, 2000, and 3000. Examples of the copolymer containing a 1,2-polybutadiene structure that can be suitably used include "Ricon 100" from TOTAL CRAY VALLEY. These conjugated diene polymers and their hydrogenated products may be modified by introducing functional groups with a compound such as maleic anhydride. When the resin or resins selected from these hydrocarbon elastomers are liquid (approximately 300,000 mPa s or less) at room temperature (25°C), in particular, the amount used is preferably 150 parts by mass or less, more preferably 1 to 30 parts by mass, and most preferably 1 to 20 parts by mass, per 100 parts by mass of the copolymer, from the viewpoints of handleability and moldability in the uncured state (handleability as a thermoplastic resin).
[0046] <Polyphenylene ether> As the polyphenylene ether (also referred to as "polyphenylene ether resin"), commercially available known polyphenylene ethers can be used. The number average molecular weight of the polyphenylene ether is arbitrary, and considering the moldability of the composition, the number average molecular weight is preferably 10,000 or less, and most preferably 5,000 or less. The number average molecular weight is preferably 500 or more.
[0047] In addition, when the composition of the present invention is added for the purpose of curing, it is preferable that the molecular end is modified with a functional group. In addition, when the composition of the present invention is added for the purpose of curing, it is preferable that one molecule has multiple functional groups. For example, it is preferable to use a modified polyphenylene ether. Examples of the functional group include radically polymerizable functional groups and functional groups such as epoxy groups, and preferably radically polymerizable functional groups. As the radically polymerizable functional group, a vinyl group is preferable. As the vinyl group, one or more of the group consisting of an allyl group, a (meth)acryloyl group, and an aromatic vinyl group are preferable, one or more of the group consisting of a (meth)acryloyl group and an aromatic vinyl group are more preferable, and an aromatic vinyl group is most preferable. That is, in the composition of the present invention, a bifunctional polyphenylene ether in which both ends of the molecular chain are modified with a radically polymerizable functional group is particularly preferable. Examples of such polyphenylene ether include Noryl (trademark) SA9000 manufactured by SABIC (modified polyphenylene ether having methacryloyl groups at both ends, number average molecular weight 2200) and bifunctional polyphenylene ether oligomer manufactured by Mitsubishi Gas Chemical Company, Inc. (OPE-2St, modified polyphenylene ether having vinylbenzyl groups at both ends, number average molecular weight 1200). Allylated PPE manufactured by Asahi Kasei Corporation can also be used. Among these, bifunctional polyphenylene ether oligomer manufactured by Mitsubishi Gas Chemical Company, Inc. (OPE-2St) can be preferably used. The amount of polyphenylene ether used in the composition of the present invention is preferably 1 to 200 parts by mass, more preferably 1 to 100 parts by mass, based on 100 parts by mass of the copolymer.
[0048] <Aromatic polyene resin> The aromatic polyene resin includes divinylbenzene reactive hyperbranched copolymers (PDV, ODV) manufactured by Nippon Steel Chemical & Material Co., Ltd. Such hyperbranched copolymers are described, for example, in the literature "Synthesis of polyfunctional aromatic vinyl copolymers and development of new IPN-type low dielectric loss materials using them" (Kawabe Masanao et al., Journal of the Japan Society of Electronics Packaging, p125-129, Vol. 12 No. 2 (2009)), U.S. Patent No. 8,404,797, and International Publication No. 2018 / 181842. Examples of aromatic polyene resins include aromatic polyene polymer resins having the above-mentioned aromatic polyene monomer as the main structural unit. The amount of aromatic polyene resin used in the composition of the present invention is preferably 1 to 200 parts by mass, more preferably 1 to 100 parts by mass, and most preferably 1 to 50 parts by mass, relative to 100 parts by mass of the copolymer. The use of the aromatic polyene resin in an amount within these ranges is effective in adjusting the mechanical properties of the cured body obtained from the composition, and is preferable in order to prevent a decrease in adhesion to other members and a decrease in toughness. When the content is 200 parts by mass or less, brittleness does not appear and adhesion to other components is improved.
[0049] <(c) Polar monomer> The polar monomer that can be used in the composition of the present invention is preferably 100 parts by mass or less per 100 parts by mass of the copolymer. The composition may not substantially contain any monomer. The polar monomer is a monomer having one or more atoms selected from oxygen, nitrogen, phosphorus, and sulfur in the molecule, and the polar monomer that can be suitably used preferably has a molecular weight of less than 5000, more preferably less than 1000, and even more preferably less than 500. The polar monomer that can be suitably used in the composition of the present invention is preferably a polar monomer that can be polymerized by a radical polymerization initiator. Examples of the polar monomer include various maleimides, bismaleimides, maleic anhydride, triallyl isocyanurate, glycidyl (meth)acrylate, tri(meth)acryl isocyanurate, and trimethylolpropane tri(meth)acrylate. Maleimides and bismaleimides that can be used in the present invention are described in, for example, International Publication No. 2016 / 114287 and JP 2008-291227 A, and can be purchased from, for example, Daiwa Kasei Kogyo Co., Ltd., Nippon Kayaku Co., Ltd., and Designer Molecules Inc. In addition, bismaleimide resin "SLK" manufactured by Shin-Etsu Chemical Co., Ltd. can also be used. These maleimide group-containing compounds are preferably bismaleimides from the viewpoints of solubility in organic solvents, high frequency characteristics, high adhesion to conductors, moldability of prepregs, and the like. These maleimide group-containing compounds may be used as polyamino bismaleimide compounds from the viewpoints of solubility in organic solvents, high frequency characteristics, high adhesion to conductors, moldability of prepregs, and the like. Polyamino bismaleimide compounds can be obtained, for example, by subjecting a compound having two maleimide groups at the terminals to a Michael addition reaction with an aromatic diamine compound having two primary amino groups in the molecule. When attempting to obtain high crosslinking efficiency with a small amount of addition, it is preferable to use a polar monomer having a multifunctional group of two or more functional groups, such as bismaleimides, triallyl isocyanurate (TAIC), and trimethylolpropane tri(meth)acrylate. The amount of the polar monomer used in the composition of the present invention is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, based on 100 parts by mass of the copolymer.By using an amount within this range, the dielectric constant and dielectric dissipation factor of the obtained cured body are prevented from becoming too high; for example, the dielectric constant can be kept at 4.0 or less, preferably 3.0 or less, and the dielectric dissipation factor can be kept at 0.005 or less, preferably 0.002 or less.
[0050] In addition, the composition of the present invention may appropriately contain "aromatic vinyl compounds" such as styrene, "aromatic polyenes" such as divinylbenzene, and "aromatic vinylene compounds" as necessary. The amount of these compounds added is arbitrary, but is preferably 100 parts by mass or less per 100 parts by mass of the copolymer. The aromatic vinylene compound refers to a compound having both a single aromatic ring or multiple condensed aromatic rings having 9 to 30 carbon atoms and a vinylene group. Examples of such aromatic vinylene compounds include indenes, beta-substituted styrenes, and acenaphthylenes. Examples of indenes include indene, various alkyl-substituted indenes, and phenyl-substituted indenes. Examples of beta-substituted styrenes include beta-alkyl-substituted styrenes such as beta-methylstyrene, and phenyl-substituted styrenes. Examples of acenaphthylenes include acenaphthylene, various alkyl-substituted acenaphthylenes, and various phenyl-substituted acenaphthylenes. As the aromatic vinylene compound, the above-exemplified compounds may be used alone or in combination of two or more. The aromatic vinylene compound preferably has a boiling point of 175° C. or more at normal pressure. From the viewpoints of industrial availability and radical polymerizability, acenaphthylene is the most preferable aromatic vinylene compound.
[0051] The composition of the present invention may further comprise one or more selected from (d) a filler, and (e) a flame retardant.
[0052] <Filling agent> If necessary, a known inorganic or organic filler can be added. These fillers are added for the purpose of controlling the thermal expansion coefficient, controlling the thermal conductivity, and reducing the cost, and the amount used is arbitrary depending on the purpose. In particular, when adding an inorganic filler, it is preferable to use a known surface modifier, such as a silane coupling agent. In particular, when the objective of the present invention is to obtain a composition excellent in low dielectric constant and low dielectric loss, the inorganic filler is preferably one or more of boron nitride (BN) or silica, and silica is more preferable. As the silica, fused silica is preferable. From the viewpoint of low dielectric properties, since the dielectric constant becomes particularly high when a large amount is added, it is preferable to use less than 500 parts by mass, more preferably less than 400 parts by mass of the filler per 100 parts by mass of the copolymer. Furthermore, in order to improve and enhance the low dielectric properties (low dielectric constant, low dielectric loss tangent), a hollow filler or a filler with a shape with many voids may be added. The average particle size (d50) of the filler is preferably 0.01 to 100 μm, more preferably 0.1 to 10 μm, and most preferably 0.3 to 1 μm. d50 is the value at 50% cumulative volume. The average particle size (d50) is determined from a volumetric particle size distribution curve obtained from a laser diffraction particle size analyzer (Beckman Coulter "Model LS-230"). Specific surface area is 1 to 30 m 2 / g is preferable, and 3 to 10m 2 / g is more preferred. The specific surface area is measured by the following method. 1 g of the sample is filled into the measurement cell, and the specific surface area is measured using a Mountech Macsorb HM model-1201 fully automatic specific surface area measuring device (BET single point method). The degassing conditions before measurement are 200°C for 10 minutes. Nitrogen is used as the adsorption gas. The volume ratio of the resin component to the filler may be in the range of 98-15:2-85, preferably 85-15:15-85, more preferably 85-30:15-70, and further preferably 80-60:20-40.
[0053] Alternatively, instead of inorganic fillers, organic fillers such as high molecular weight polyethylene or ultra-high molecular weight polyethylene can be used. From the viewpoint of heat resistance, it is preferable that the organic fillers themselves are crosslinked, and they are preferably blended in the form of fine particles or powder. These organic fillers can suppress increases in the dielectric constant and dielectric loss tangent.
[0054] On the other hand, by mixing and dispersing a high dielectric constant insulating filler having a dielectric constant of preferably 4 to 10,000, more preferably 5 to 10,000 at 1 GHz in the composition of the present invention, it is possible to produce an insulating cured body having a high dielectric constant insulating layer having a dielectric constant of preferably 4 to 20 while suppressing an increase in dielectric loss tangent (dielectric loss). By increasing the dielectric constant of a film made of an insulating cured body, it is possible to miniaturize circuits and increase the capacity of capacitors, which can contribute to miniaturization of high frequency electrical components. An insulating layer having a high dielectric constant and a low dielectric loss tangent is suitable for applications such as capacitors, inductors for resonant circuits, filters, and antennas. Examples of the high dielectric constant insulating filler used in the present invention include inorganic fillers or metal particles that have been subjected to an insulating treatment. Specific examples are known high dielectric constant inorganic fillers such as barium titanate and strontium titanate, and other examples are specifically described in, for example, JP-A-2004-087639.
[0055] <Flame retardants> A flame retardant can be used in the composition of the present invention. In terms of maintaining a low dielectric constant and a low dielectric loss tangent, the preferred flame retardant is at least one selected from organic phosphorus-based flame retardants such as phosphoric acid esters or condensates thereof, bromine-based flame retardants, and red phosphorus. In particular, among phosphoric acid esters, compounds having multiple xylenyl groups in the molecule are preferred in terms of flame retardancy and low dielectric loss tangent.
[0056] In addition to the flame retardant, antimony compounds such as antimony trioxide, antimony tetraoxide, antimony pentoxide, and sodium antimonate, or nitrogen-containing compounds such as melamine, triallyl-1,3,5-triazine-2,3,4-(1H,3H,5H)-trione, and 2,4,6-triaryloxy-1,3,5-triazine may be added as a flame retardant assistant. The total amount of these flame retardants and flame retardant assistants is usually preferably 1 to 100 parts by mass per 100 parts by mass of the composition. In addition, 30 to 200 parts by mass of the polyphenylene ether (PPE) resin having a low dielectric constant and excellent flame retardancy may be used per 100 parts by mass of the flame retardant.
[0057] The composition of the present invention may further contain (f) a solvent. Among the compositions of the present invention, those that are particularly liquid due to the inclusion of a solvent are called varnishes.
[0058] <Solvent> An appropriate solvent may be added to the composition of the present invention as necessary. The amount of the solvent is not particularly limited. The solvent is used to adjust the viscosity and fluidity of the composition. In particular, when the composition of the present invention is in the form of a varnish, a solvent is preferably used. As the solvent, if the boiling point under atmospheric pressure is too low, that is, if the volatility is too high, the thickness of the applied film may become uneven, so a solvent with a certain boiling point or higher is preferable. The preferred boiling point is about 100°C or higher, more preferably 110°C or higher and 300°C or lower under atmospheric pressure. Examples of the solvent include cyclohexane, toluene (boiling point 110°C), ethylbenzene, xylene, mesitylene, tetralin, acetone, limonene, mixed alkanes, mixed aromatic solvents, etc. The amount of the solvent used in the composition of the present invention is arbitrary, but is preferably 5 to 500 parts by mass, more preferably 10 to 300 parts by mass, and most preferably 50 to 150 parts by mass, relative to 100 parts by mass of the copolymer.
[0059] The composition and varnish of the present invention may contain additives that are usually used in resins, such as antioxidants, weathering agents, light stabilizers, lubricants, compatibilizers, antistatic agents, etc., within the scope of not impairing the effects and objects of the present invention. The composition and varnish of the present invention are obtained by mixing, dissolving or melting the various additives described above, and any known method can be used for mixing, dissolving and melting.
[0060] <Varnish> The varnish of the present invention can be made viscous liquid at room temperature or by heating to 100°C or less by adjusting the composition and molecular weight of the copolymer used, adding a certain amount or more of liquid monomer or solvent within the range of the present invention, or adding a liquid flame retardant, and has a viscosity of, for example, hundreds of thousands of mPa·s or less at room temperature, preferably 2000 mPa·s or less, more preferably 1000 mPa·s or less, and most preferably 500 mPa·s or less. Here, the viscosity is measured, for example, by a rotational viscometer. Specifically, it can be applied, impregnated, filled, or dropped onto other materials by an appropriate method, and a molded body can be obtained by removing the solvent. It can then be cured by heat or light to obtain the desired cured body. Such properties can be obtained by applying various transfer molding (pressure molding), applying on or between substrates or semiconductor device materials, forming into sheets or films by extrusion lamination or spin coating, and then curing, to form a multilayer structure including an insulating layer I.
[0061] <Multilayer structure including insulating layer> The insulating layer formed from the composition of the present invention is in the form of a sheet. Its thickness is arbitrary, but is preferably in the range of 10 μm to 1 mm. These compositions can exhibit the properties of thermoplastic resins. Therefore, under conditions that do not cause crosslinking, the composition can be formed into a shape such as a sheet in a substantially uncured state by a known molding method for thermoplastic resins, such as extrusion molding, injection molding, press molding, inflation molding, etc., and then crosslinked (cured) by laminating with other layers. In addition, for example, when the composition is a varnish, it can be applied to a smooth surface of another substrate, such as a copper foil, and then the solvent can be removed by heating, decompression, air drying, etc., to form a molded body in the form of a sheet or film, which can then be laminated and crosslinked (cured). It is also possible to impregnate a porous substrate, woven fabric, or nonwoven fabric with the varnish of the present invention, remove the solvent, obtain a composite sheet, and use this as the multilayer structure. These sheets may be uncured (semi-cured) to the extent that they can maintain the sheet shape, or may be completely cured. The degree of curing of the composition can be quantitatively measured by a known dynamic viscoelasticity measurement method (DMA, Dynamic Mechanical Analysis).
[0062] <Curing> The multilayer structure can be cured by a known method, taking into consideration the curing conditions (temperature, time, pressure, light) of the raw materials and curing agent contained therein. When the curing agent used is a peroxide, the curing conditions, such as the heating conditions, can be determined, generally, taking into consideration the half-life temperature and the like disclosed for each peroxide.
[0063] <Hardened multi-layer structure> The cured product of the multilayer structure of the present invention can be sufficiently cured, and the gel content of the cured product of the insulating layer measured according to ASTM may be 90% by mass or more. In addition, in the measurement range of 10 to 50 GHz, particularly preferably at 10 GHz, the cured product of the insulating layer preferably has a dielectric constant of 3.0 to 2.0, more preferably 2.8 to 2.0, and most preferably 2.5 to 2.0. The dielectric loss tangent is preferably 0.003 to 0.0005, and more preferably 0.002 to 0.0008. In addition, the volume resistivity of the obtained cured product of the insulating layer is preferably 1×10 15 The electrical insulating material preferably has a surface hardness of Ω·cm or more and a water absorption rate of 0.1 mass % or less. These values are particularly preferable for an electrical insulating material for high frequencies of 3 GHz or more.
[0064] The cured product of the insulating layer contained in the multilayer structure has high adhesion to the smooth surface of copper foil for wiring. The adhesive strength is preferably 0.8 N / mm or more, more preferably 1.0 N / mm or more. Therefore, it is particularly preferable as an interlayer insulating material or a coverlay. At least a part or at least one surface of the interlayer insulating material used in multilayer CCL or FCCL must be adhered to the smooth surface of the copper foil. The cured product of the above composition is preferable for this application because it shows high adhesion to the smooth surface of the copper foil. In addition, since the coverlay needs to be adhered to the smooth surface of the copper foil on the substrate at its lower surface, it can be said that the cured product of the present composition is also preferable because it shows high adhesion to the smooth surface of the copper foil.
[0065] Examples of methods for producing a high-frequency transmission line, antenna, and multilayer board (CCL, FCCL) having the multilayer structure of the present invention include the following methods. A method in which a composition is applied as a varnish onto a substrate (resin layer) that has a smooth copper foil surface open on the upper surface by bonding with a roughened copper foil surface, the solvent is removed, an insulating layer is formed, and then another resin layer surface is laminated to form a multilayer structure, which is treated under appropriate temperature and pressure conditions to harden and bond, to produce a multilayer board. Alternatively, a method in which a previously prepared uncured sheet is placed as an insulating layer onto a substrate (resin layer) that has a smooth copper foil surface open on the upper surface by bonding with a roughened copper foil surface, and another resin layer surface is laminated to form a multilayer structure, which is treated under appropriate temperature and pressure conditions to harden and bond, to produce a multilayer board, can also be exemplified.
[0066] Examples of methods for manufacturing a substrate having a coverlay include the following processes. A method of applying a composition as a varnish onto a substrate having a smooth copper foil surface open on the upper surface by adhering to a roughened copper foil surface, removing the solvent, and then applying pressure and heat under predetermined conditions to harden the insulating layer to form a coverlay. Alternatively, a method of overlaying an uncured sheet of a composition prepared in advance onto a substrate having a smooth copper foil surface open on the upper surface by adhering to a roughened copper foil surface, applying pressure and heat to harden and bond the insulating layer can also be exemplified.
[0067] From another viewpoint, the present invention provides an interlayer insulating material including a cured product of a composition containing an olefin-aromatic vinyl compound-aromatic polyene copolymer as a main component and containing 0.001 to 10 parts by mass of a silane coupling agent relative to the olefin-aromatic vinyl compound-aromatic polyene copolymer, and also provides a high-frequency transmission line such as a microstrip line, an antenna, a multilayer CCL substrate, or a multilayer FCCL substrate, which includes the interlayer insulating material. The interlayer insulating material layer is an interlayer insulating material at least a part of which or one surface of which is in contact with a smooth copper foil surface. The layer made of the interlayer insulating material is characterized by good low dielectric performance, heat resistance, and high adhesion to the smooth copper foil surface of a substrate.
[0068] From another viewpoint, the present invention is a coverlay including a cured product of a composition containing an olefin-aromatic vinyl compound-aromatic polyene copolymer as a main component and containing 0.001 to 10 parts by mass of a silane coupling agent relative to the olefin-aromatic vinyl compound-aromatic polyene copolymer, and also a substrate including the coverlay. At least the lower surface of the coverlay is in contact with the smooth copper foil surface of the substrate. The coverlay is characterized by the excellent low dielectric performance and heat resistance, and high adhesion to the smooth copper foil surface of the substrate.
[0069] Also, the insulating layer of the present invention can be bonded to a resin layer of another resin-based material used in CCL or FCCL by a known method. For example, a method of performing corona treatment or plasma treatment on the resin layer in advance to activate the surface, or a method of forming irregularities on the surface to roughen it, can be exemplified. Furthermore, the insulating layer made of the composition of the present invention can exhibit a high adhesive strength to, for example, polyimide (PI), liquid crystal polymer (LCP), polyphenylene ether (PPE), polyfunctional aromatic vinyl resin (ODV), epoxy resin, or each resin having the same composition as the insulating layer I, or a sheet thereof, compared to a case in which a surface modifier is not added. In particular, when the surface of these resin sheets is treated by a surface treatment such as corona treatment or plasma treatment as described above, a higher adhesiveness can be expected. EXAMPLES
[0070] The present invention will be described below with reference to examples, but the present invention should not be construed as being limited to the following examples. The copolymers obtained in the Synthesis Examples and Comparative Synthesis Examples were analyzed by the following methods.
[0071] The content of vinyl group units derived from ethylene, hexene, styrene, and divinylbenzene in the copolymer is determined by: 1 The measurements were performed using H-NMR from the peak area intensities assigned to each compound. The sample was dissolved in deuterated 1,1,2,2-tetrachloroethane, and the measurements were performed at 50 to 130°C.
[0072] The molecular weight was determined as a number average molecular weight (Mn) converted to standard polystyrene using GPC (gel permeation chromatography) under the following conditions.
[0073] Column: Two TSK-GEL MultiporeHXL-M φ7.8×300 mm (Tosoh Corporation) columns were connected in series. Column temperature: 40℃ Solvent: THF Flow rate: 1.0ml / min. Detector: RI detector
[0074] <Gel content> The gel fraction was determined as the boiling toluene insoluble matter according to ASTM D2765-84.
[0075] <Water absorption rate> The water absorption rate was measured after immersion in pure water at 23°C for 24 hours in accordance with ASTM D570-98.
[0076] <Dielectric constant and dielectric loss (dielectric tangent)> The dielectric constant and dielectric loss tangent were measured using the cavity resonator perturbation method (Agilent Technologies 8722ES network analyzer, Kanto Electronics Application Development Co., Ltd. cavity resonator) at 23°C and 10 GHz using a 1 mm x 1.5 mm x 80 mm sample cut from the sheet.
[0077] <Volume resistivity> The measurement was performed at room temperature using a film approximately 0.5 mm thick in accordance with JIS K6911:2006.
[0078] <Adhesion strength between insulating layer and smooth surface of copper foil (peel strength)> The copper foil used was manufactured by Mitsui Mining & Smelting Co., Ltd. (VSP series, TQ-M7-VSP, thickness 12 μm, roughened surface roughness Rz 1.1 μm). The copper foil was placed on a Teflon (registered trademark) sheet with the smooth surface facing up, and several uncured sheets, which are the insulating layer I, were placed on the smooth surface, and a SUS mold (thickness 0.2 mm) was placed on top of the uncured sheets. The Teflon sheet was then placed on top of the uncured sheets, and a load of 5 MPa was applied using a press machine, and the sheets were heated at 120°C for 30 minutes, 150°C for 30 minutes, and then 200°C for 120 minutes to be cured. Here, the insulating layer I is the uncured sheet of the examples and comparative examples described below. After curing, the Teflon sheet and the mold were removed, and a multilayer structure was obtained in which the sheet and the copper foil were bonded and cured. The adhesion strength with the copper foil was measured in accordance with Japan Industrial Standards (JIS) C6471:1995, and the peeling was evaluated at 180° peeling. For reference, the roughened surface of the copper foil was placed on the Teflon sheet by the above method, and several uncured sheets were placed on the roughened surface to obtain a laminate bonded and cured with the roughened surface of the copper foil, and the adhesion strength was measured in the same manner.
[0079] <Production of copolymer> Synthesis examples P-1, P-2 With reference to the manufacturing methods described in JP 2009-161743 A and JP 2010-280771 A, polymerization was carried out using Rac-dimethylmethylenebis(4,5-benzo-1-indenyl)zirconium dichloride (see formula (1) below for structure) as a catalyst, modified methylaluminoxane (Tosoh Finechem, MMAO-3A toluene solution) as a cocatalyst, cyclohexane as a solvent, styrene, divinylbenzene, ethylene, and 1-hexene as raw materials as necessary, in an autoclave with a capacity of 10 L and a stirrer and a jacket for heating and cooling. 1-Isopropanol was added to the obtained polymerization liquid, and then a large amount of methanol was added to recover the copolymer. The copolymer was air-dried and further vacuum-dried at 30°C for one day and night to obtain copolymers P-1 and P-2. Table 1 shows the composition and number average molecular weight of the copolymers.
[0080] Formula (1) [ka]
[0081] Synthesis example P-3 With reference to the manufacturing methods described in JP-A-9-40709, JP-A-9-309925, JP-A-2009-161743, and JP-A-2010-280771, polymerization was carried out using dimethylmethylenebiscyclopentadienylzirconium dichloride (see formula (2) below for structure) as a catalyst, modified methylaluminoxane (Tosoh Finechem, MMAO-3A toluene solution) as a cocatalyst, cyclohexane as a solvent, and styrene, divinylbenzene, and ethylene as raw materials in an autoclave with a capacity of 10 L and a stirrer and a jacket for heating and cooling. 1-Isopropanol was added to the obtained polymerization liquid, and then a large amount of methanol was added to recover the copolymer. The copolymer was spread thinly in a large container and vacuum dried at 30°C for two days and nights. Table 1 shows the composition and number average molecular weight of copolymer P-3.
[0082] Formula (2) [ka]
[0083] The other raw materials are as follows: For the bifunctional polyphenylene ether oligomer (OPE-2St, number average molecular weight 1200), a toluene solution product manufactured by Mitsubishi Gas Chemical Company, Inc. was diluted with toluene, a large amount of methanol was added, methanol precipitation was performed, air dried, and then dried under reduced pressure to obtain a powdered polyphenylene ether oligomer. For the 1,2-polybutadiene, Nippon Soda Co., Ltd.'s "B-3000", number average molecular weight 3200, viscosity 210 Poise (21000 mPa s, 45°C) was used. For the BMI, Daiwa Kasei Kogyo Co., Ltd.'s BMI-5100 (3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide) was used. The silane coupling agents used were KBM-503 (3-methacryloxypropyltrimethoxysilane), KBM-403 (3-glycidoxypropyltrimethoxysilane), and KBM-1403 (p-styryltrimethoxysilane) manufactured by Shin-Etsu Silicone Co., Ltd. The curing agent used was Perhexyne 25B (organic peroxide, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3) manufactured by NOF Corporation.
[0084] [Table 1]
[0085] [Table 2]
[0086] [Table 3]
[0087] Example 1 Using a vessel equipped with a heating and cooling jacket and stirring blade, P-1 (ethylene-styrene-divinylbenzene copolymer) obtained in the synthesis example, a solvent (toluene), and a silane coupling agent KBM-503 were heated to about 40°C in the ratio of Table 2, and stirred to dissolve the copolymer. Furthermore, 1 part by mass of a curing agent (dicumyl peroxide) was added to 100 parts by mass of the resin components excluding the curing agent, solvent, and silane coupling agent, dissolved, stirred, and mixed to obtain a varnish-like composition. The obtained composition was poured into a silicon mold (frame length 7 cm, width 7 cm, thickness 0.5 mm, 1.0 mm, or 2.0 mm) on a Teflon sheet placed on a glass plate, air-dried, and then further dried in a vacuum dryer at 60°C for 3 hours or more to obtain an uncured sheet. Furthermore, the obtained uncured sheet was placed in a press under a load of 5 MPa, a Teflon sheet and a SUS mold were placed thereon, and the sheet was heat-treated at 120°C for 30 minutes, 150°C for 30 minutes, and then 200°C for 120 minutes. The Teflon sheet and the SUS mold were then removed to obtain a cured sheet.
[0088] Examples 2 to 9, Comparative Examples 1 and 2 Curable compositions were prepared according to the formulations in Tables 2 or 3 (units in the tables are parts by mass) in the same manner as in Example 1, and uncured sheets and cured sheets of the compositions of the Examples and Comparative Examples were obtained in the same manner.
[0089] The gel fraction, dielectric constant, dielectric tangent, water absorption and volume resistivity of the cured sheet are shown in Tables 2 and 3. The adhesive strength of the interface of the cured product of the multilayer structure consisting of the smooth copper foil surface and the insulating layer I, which was obtained by the above method, was measured, and the results are shown in Tables 2 and 3. Here, the insulating layer I is an uncured sheet of the examples and comparative examples. In the case of the examples, when the adhesive strength of the interface between the smooth copper foil surface and the insulating layer I was measured, the adhesive strength was too high, and when the value of 1 N / mm or more was shown, the resin part broke (material break) or stretched, or the copper foil broke (material break). That is, in these cases, the adhesive strength was 1 N / mm or more. In contrast, Comparative Examples 1 and 2 showed values of 0.4 N / mm and 0.3 N / mm, respectively. For reference, the adhesive strength of the interface between the roughened copper foil surface and the insulating layer I was measured in the same manner, and all the samples of the examples and comparative examples showed adhesive strengths of 1 N / mm or more, as described above. That is, the composition of this example can give a cured product that shows high adhesive strength to both the smooth and roughened copper foil surfaces.
[0090] Example 10 Using the same apparatus as in Example 1, P-1 (ethylene-styrene-divinylbenzene copolymer), toluene, silane coupling agent KBM-503, and curing agent (dicumyl peroxide) were added and dissolved in 1 part by mass per 100 parts by mass of the resin component, and mixed with stirring to obtain a varnish-like composition. Silica filler (SFP-130MC manufactured by Denka Co., Ltd., d50 = 0.6 μm, specific surface area 6.2 m) was added to the mixture. 2 / g, density 2.2g / cm 3 ) was added and stirred to make a slurry-like varnish. 30 vol% of silica filler was used for 70 vol% (volume %) of the resin component. 1 part by mass of the hardener was added for a total of 100 parts by mass of the resin raw materials other than the hardener, solvent, silane coupling agent, and filler.
[0091] Example 11 The structure (2) shown in Fig. 2 was prepared. Here, the resin layer A was made of polyimide, and the insulating layer I and the resin layer B were made of a composition containing the copolymer of the present invention. A multilayer sheet (commercial product, Upicel N, polyimide film 25 μm, electrolytic copper foil 18 μm, single-sided copper-clad type) was prepared in which the roughened surface of the copper foil was bonded to the polyimide (PI) sheet. Furthermore, an uncured sheet having a thickness of 500 μm obtained in the same manner as in Example 10 was prepared. The copper foil was manufactured by Mitsui Mining & Smelting Co., Ltd. (VSP series, TQ-M7-VSP). An uncured sheet having a thickness of 100 μm (insulating layer I) obtained in the same manner as in Example 5 was placed on the open copper foil smooth surface of the multilayer sheet in which the roughened surface of the copper foil was bonded to the polyimide (PI) sheet, and further an uncured sheet having a thickness of 100 μm obtained in Example 10 (resin layer B) was placed on the uncured sheet, and further a copper foil was placed on the uncured sheet so that the roughened surface of the copper foil was in contact with the resin layer B. A thin Teflon sheet was partially inserted between the smooth copper foil surface and the uncured sheet (insulating layer I) of Example 5, and cured under pressure with a press machine under the same conditions as in Example 1, and a multilayer structure sheet was obtained in which the resin layer A (polyimide) / copper foil / insulating layer I / resin layer B (Example 10) / copper foil were laminated and bonded from the bottom. After curing, the inserted Teflon sheet was removed to trigger a tensile test, and the adhesive strength between the smooth copper foil surface and the insulating layer I was obtained. Similarly, a thin Teflon sheet was partially inserted between the insulating layer I and the resin layer B, and the adhesive strength between the insulating layer I and the resin layer B of the multilayer structure sheet obtained by curing in the same manner was obtained. In all samples, when the adhesive strength was 1 N / mm or more, the resin part broke (material breakage) or stretched, or the copper foil broke (material breakage). That is, in these cases, the adhesive strength between the smooth copper foil surface and the insulating layer I, and between the insulating layer I and the resin layer B was 1 N / mm or more. Furthermore, the adhesive strength between a commercially available polyimide (PI) and a roughened copper foil surface was also measured separately and was found to be 1 N / mm or more. From the above, it is understood that the multilayer structure of the present invention has strong adhesive strength between each interface.
[0092] Example 12 A structure (4) shown in FIG. 3 was prepared. Here, the insulating layer I was made of a composition containing the copolymer of the present invention, and the resin layers A and B were both made of polyimide (PI). An uncured sheet having a thickness of 100 μm (insulating layer I) obtained in the same manner as in Example 6 was placed on the open copper foil smooth surface of a multilayer sheet (commercially available, the same as in Example 11) in which the roughened surface of the copper foil was bonded to a polyimide (PI) sheet, and a multilayer sheet (commercially available) in which the roughened surface of the copper foil was bonded to a polyimide (PI) sheet was placed on top of the uncured sheet so that the open copper foil smooth surface was in contact with the uncured sheet. The multilayer sheet was pressed with a press machine under the same conditions as in Example 1, and the resin layer A (polyimide) / copper foil / insulating layer I / copper foil / resin layer B (polyimide) were laminated and bonded in this order from the bottom to obtain a multilayer structure sheet. As in Example 11, a thin Teflon sheet was inserted between the smooth copper foil surface and the uncured sheet (insulating layer I) of Example 6 before curing, and the thin Teflon sheet was removed to trigger a tensile test and determine the adhesive strength between the smooth copper foil surface and insulating layer I. As a result, when the adhesive strength reached 1 N / mm or more, the resin broke (material breakage). In other words, the adhesive strength between the smooth copper foil surface and insulating layer I was 1 N / mm or more.
[0093] Example 13 The basic unit structure shown in FIG. 1 was prepared. Here, the insulating layer I was made of the copolymer composition of the present invention, and the resin layer A was made of polyimide. An uncured sheet with a thickness of 500 μm (insulating layer I) obtained in the same manner as in Example 2 was placed on the open copper foil smooth surface of a multilayer sheet (commercially available, the same as in Example 11) in which the roughened surface of the copper foil was bonded to a polyimide (PI) sheet, and a thin Teflon sheet was partially inserted between the copper foil smooth surface and the uncured sheet (insulating layer I). The sheet was cured and bonded under pressure with a press machine under the same conditions as in Example 1, to obtain a cured sheet with a multilayer structure consisting of resin layer A (polyimide) / copper foil / insulating layer I. The inserted Teflon sheet was removed to trigger a tensile test, and the adhesive strength between the copper foil smooth surface and the insulating layer I was determined. As a result, when the adhesive strength was 1 N / mm or more, the resin part broke (material breakage) or stretched, or the copper foil broke (material breakage). In other words, the adhesive strength between the smooth surface and the insulating layer I was 1 N / mm or more.
[0094] Example 14 The basic unit structure shown in FIG. 1 was prepared. The copper foil used was manufactured by Mitsui Mining & Smelting Co., Ltd. (VSP series, TQ-M7-VSP). Here, both the insulating layer I and the resin layer A were made of the copolymer composition of the present invention. Copper foil was placed on the uncured sheet (resin layer A) of 500 μm thickness obtained in the same manner as in Example 10 so that the roughened surface was in contact with the copper foil, and the uncured sheet (insulating layer I) of 500 μm thickness obtained in the same manner as in Example 2 was placed on the smooth surface of the copper foil, and a thin Teflon sheet was partially inserted between the smooth copper foil surface and the uncured sheet (insulating layer I), and the sheets were cured and bonded under pressure with a press machine under the same conditions as in Example 1 to obtain a multilayer cured sheet consisting of resin layer A (Example 10) / copper foil / insulating layer I. The inserted Teflon sheet was removed to trigger a tensile test, and the adhesive strength between the smooth copper foil surface and the insulating layer I was determined. As a result, when the adhesive strength was 1N / mm or more, the resin broke (material breakage) or stretched, or the copper foil broke (material breakage). In other words, the adhesive strength between the smooth surface and the insulating layer I was 1N / mm or more.
[0095] The cured product of the insulating layer made of the composition of the present invention shows a high gel content and is sufficiently cured, and can show a low dielectric constant, a low dielectric loss tangent, a low water absorption rate, and a high resistivity. The cured product of the multilayer structure of the present invention can show high adhesive strength not only to the roughened surface of the copper foil but also to the smooth surface of the copper foil. Therefore, it is possible to have high adhesiveness between each layer, and the cured product of the multilayer structure is useful as an interlayer insulating layer (interlayer insulating material) or coverlay for high-frequency transmission lines, multilayer CCLs, multilayer FCCLs, or antennas.
Claims
1. one or more insulating layers; One or more resin layers; At least one copper foil having a smooth surface and a roughened surface; A method for producing a multilayer structure comprising: the insulating layer comprises an olefin-aromatic vinyl compound-aromatic polyene copolymer and / or an olefin-aromatic polyene copolymer and a surface modifier; the resin layer includes at least one selected from the group consisting of polyimide (PI), liquid crystal polymer (LCP), polyphenylene ether (PPE), polyfunctional aromatic vinyl resin (ODV), epoxy resin, and a composition identical to that of the insulating layer; The manufacturing method includes: a step of adhering a roughened surface of a first copper foil to at least one surface of a first resin layer, leaving a smooth surface of the first copper foil and a portion of the surface of the first resin layer in an open state; applying a varnish containing at least the olefin-aromatic vinyl compound-aromatic polyene copolymer and / or the olefin-aromatic polyene copolymer to the smooth surface of the first copper foil and a portion of the surface of the first resin layer that is open; removing solvent from the applied varnish and forming a first insulating layer on the smooth surface of the first copper foil and a portion of the surface of the first resin layer. Including, In the multilayer structure, At least one surface of each of the insulating layers is bonded to the smooth surface of the copper foil, and For each of the resin layers, at least one surface of the resin layer is bonded to the roughened surface of the copper foil and the resin layer is not bonded to the smooth surface of the copper foil, or both surfaces of the resin layer are not bonded to the copper foil. A manufacturing method comprising:
2. one or more insulating layers; One or more resin layers; At least one copper foil having a smooth surface and a roughened surface; A method for producing a multilayer structure comprising: the insulating layer comprises an olefin-aromatic vinyl compound-aromatic polyene copolymer and / or an olefin-aromatic polyene copolymer and a surface modifier; the resin layer includes at least one selected from the group consisting of polyimide (PI), liquid crystal polymer (LCP), polyphenylene ether (PPE), polyfunctional aromatic vinyl resin (ODV), epoxy resin, and a composition identical to that of the insulating layer; The manufacturing method includes: a step of adhering a roughened surface of a first copper foil to at least one surface of a first resin layer, leaving a smooth surface of the first copper foil and a portion of the surface of the first resin layer in an open state; preparing an uncured sheet comprising at least the olefin-vinyl aromatic compound-aromatic polyene copolymer and / or the olefin-aromatic polyene copolymer; placing the uncured sheet on the smooth surface of the first copper foil and a portion of the surface of the first resin layer that are open to form a first insulating layer; Including, In the multilayer structure, At least one surface of each of the insulating layers is bonded to the smooth surface of the copper foil, and For each of the resin layers, at least one surface of the resin layer is bonded to the roughened surface of the copper foil and the resin layer is not bonded to the smooth surface of the copper foil, or both surfaces of the resin layer are not bonded to the copper foil. A manufacturing method comprising:
3. moreover forming a second resin layer that does not adhere to any of the copper foils; The method according to claim 1 or 2, comprising:
4. moreover removing a portion of the first copper foil by etching to leave a smooth surface of the first copper foil and a portion of the surface of the first resin layer open. The method according to claim 1 or 2, comprising:
5. The method according to claim 1 or 2, wherein the surface modifying agent is a silane coupling agent.
6. The method according to claim 1 or 2, wherein the olefin-aromatic vinyl compound-aromatic polyene copolymer and / or the olefin-aromatic polyene copolymer satisfies all of the following conditions (1) to (4): (1) The number average molecular weight of the copolymer is 500 or more and less than 100,000. (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0 to 98 mass %. (3) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of the vinyl groups and / or vinylene groups derived from the aromatic polyene units is 1.5 or more and less than 20 per number average molecular weight. (4) The olefin is one or more olefins selected from olefins having 2 to 20 carbon atoms, the content of the olefin monomer units is 10 mass% or more, and the total of the olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is 100 mass%.
7. A step of curing the multilayer structure obtained by the method according to claim 1 or 2. A method for producing a cured multi-layer structure comprising:
8. The method of claim 7 , wherein the curing step comprises applying heat and / or pressure.
Citation Information
Patent Citations
Thermosetting resin composition having low dielectric constant
JP1994192392A
Electronic part for high frequency using low dielectric loss tangent insulating material
JP2004087639A
Cross-copolymerized olefin / styrene / diene copolymer, process for the production of the same and uses thereof
JP2007217706A
Post curing resin composition and high frequency electrical insulating material using the same
JP2009161743A
Post-curable resin composition and electrical insulating material using the same
JP2010280771A